Pengaruh Pemberian Susu Formula MenggunakanBotol Susu (Dot) Terhadap Kejadian RampanKaries Pada Anak PrasekolahDi Kelurahan Pabelan - PURWANINGSIH, ANI, Agus Sudaryanto, S.Kep., Ns., M.Kes, Arif Widodo, A.Kep.M.Kes (2016)
Rampan caries is caries which occurs very quickly and on a few teeth and often cause pain that is difficult to eat and fussy child. Early childhood caries occur in the newly erupted teeth and pre-school children. Patterns of consumption that are less precise formula as way of presentation that uses bottled associated with duration of administration, frequency, and timing can cause caries in children. This study aims to determine the effect of formula feeding using milk bottles (dot) on the incidence of caries in preschool children Rampan in Sub Pabelan. This study uses a quantitative research with retrospective approach. Sample research is pre-school age children in Sub Pabelan District of Kartasura that as many as 60 children with purposive sampling technique. Collecting data using questionnaires and documentation were analyzed using Chi Square test. Conclusion of the study are (1) the frequency of administration of formula in bottles in preschool children who experience Rampan caries are mostly more than 3 bottles per day, (2) time to drink formula in a bottle in preschool children who experience Rampan caries mostly 6 months or more , (3) provision of sugar composition in the formula in the bottle of milk in preschool children experiencing dental caries mostly not add sugar composition in the formula, (4) there is influence of the frequency of infant formula in the bottle on the incidence Rampan caries in preschool children, ( 5) there are significant time drinking milk formula in a bottle against Rampan incidence of caries in preschool children, (6) there is no effect of sugar composition in the formula in a bottle against Rampan incidence of caries in preschool children in Sub Pabelan. Keywords: frequency, time to drink, sugar composition, Rampan caries, preschoolers